The Role of Oxidative Stress in the Induction and Development of Psoriasis - Alexander Blagov; Vasily Sukhorukov; Shuzhen Guo; Dongwei Zhang; Ilya Eremin; Alexander Orekhov (Frontiers in Bioscience-Landmark, 2023)
Psoriasis cannot be completely cured and is often difficult to diagnose, which is why the search for new effective therapies and diagnostics is a highly relevant area of research. To identify new therapeutic compounds, the first step is to study the role of various factors underlying the development of psoriasis. One such factor is oxidative stress. In this review, we will consider the role of oxidative stress at different stages of psoriasis development, as well as biomarkers of oxidative stress that can potentially be used in the diagnosis of psoriasis and antioxidants, which are likely to be applied in the treatment of this disease.